Implementasi Strategi Digital dan Rebranding Produk Handmade Lokal: Studi Kasus Transformasi Raitalexander - Raita Syaumi Emira Rachman (Ikatan Da'i Indonesia, 2025)
Indonesia’s handmade fashion industry holds significant potential for growth but continues to face challenges in building a premium image and competing in global markets. Digital transformation and rebranding have emerged as strategic solutions to enhance the competitiveness of local handmade products. This study aims to analyze the implementation of digital strategies and rebranding in Raitalexander, a handmade brand from Bandung striving to establish itself as a premium brand. The research employed a case study with a descriptive approach, involving observations of digital channels (Instagram, website, e-commerce) and strategic analysis using the SOSTAC Framework and 7P Marketing Mix. The findings reveal that the implementation of a new visual identity, culturally rooted storytelling, omnichannel distribution, and influencer collaboration successfully increased digital engagement, achieving over 3.9 million views within three months and a 12.8% rise in profile visits. The discussion highlights that brand identity consistency, structured digital planning, and market education on premium value are key factors behind this success. In conclusion, integrated digital strategies and rebranding can strengthen the brand equity of local handmade products, enhance their appeal to urban consumers, and open opportunities for international market penetration. These findings provide practical insights for other creative businesses seeking sustainable transformation.